Special Measures of Child Protection in Criminal Proceedings - Stevanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
In this paper, the author is pointing towards the steps taken on the normative level by the state as well as by the international community with the aim to improve the rights of a child victim of all types of sexual exploitation and sexual abuse in the criminal proceedings, i.e. the application of the concept of ”child-friendly justice”. This paper also gives an overview of certain project activities aimed towards the implementation of concrete solutions which should fulfil this demand.